ANALISIS PENGGUNAAN DANA DESA PADA MASA PANDEMI COVID-19 (Studi Desa Sebasang Kecamatan Moyo Hulu) - Subhan Purwadinata; S Syafruddin; Tita Yuliarsih (Jurnal Ekonomi & Bisnis, 2021)
This study aims to describe the use of village funds in fiscal year of 2020 in handling COVID-19 pandemic in Sebasang Village, Moyo Hulu Sub-district. This study was descriptive qualitative. Method used to collect data were interview and literature study. The informants in this study were the Village head, Village Secretary, Treasurer, head of Consultative Board Village (BPD), Professional village Facilitator, one of beneficiaries communities during Covid-19 pandemic. The data used in this study was qualitative which used as field data that try to observe, to know and to describe the factual condition in the field. The data were analyzed using interactive analysis of Miles and Huberman. The results of study showed that the use of village funds during the COVID-19 pandemic was still based on the provisions regulation of Ministry of Villages, Development of Disadvantaged Regions, and Transmigration of the Republic of Indonesia Number 6 year of 2020 concerning amendments to regulation of Ministry of Villages, Development of Disadvantaged Regions, and Transmigration of the Republic of Indonesia number 11 year of 2019 concerning priorities for the use of village funds in year of 2020. Explicitly that the regulation of amendment state that village fund can be used for basic social prevention especially public health in village for example regulate about healthy campaign and clean lifestyle in village. The use of village funds in Sebasang village, MoyoHulu sub-district itself was more focused toward COVID-19 response villages and direct cash aid from village funds (BLT-DD in the era of the COVID-19 pandemic).